Bringing Identification of Empirically Supported Treatments Into the 21st Century. (9th November 2015) - Chambless, Dianne L.
Abstract : The author applauds the plan proposed by Tolin, McKay, Forman, Klonsky, and Thombs (2015) for bringing the methodology for identifying empirically supported treatments (ESTs) into the 21st century. She suggests that further attention is required to operationalize (a) what sorts of designs for effectiveness studies will be acceptable to the Committee on Science and Practice, (b) how data on improvement in functioning will be incorporated in the context of brief treatments, and (c) how complications in obtaining clean follow‐up data for long‐term outcomes will be addressed, and to specify (d) whether noninferiority to an existing EST is acceptable evidence of efficacy. She further cautions that meta‐analyses can mask poorly designed studies and bias in their implementation that will require the Committee's careful scrutiny.